Economic technologies for disinfection and decontamination of water, advances in Argentina - Navntoft, Christian (2010)
R. Pizarro, Galo Soler-Illia, Laura Dawidowski, Marta I. Litter, Miguel A. Blesa, María C. Apella, Margarita del V. Hidalgo, María G. García, Priscilla Powell, María Puchulu, D. Fernández Water is a fluid process of great importance in Nuclear Technology. Chemical Activity Unit (UAQ) has devoted much effort to the study of fundamental properties and applications in order to optimize the operation of cooling systems, and auxiliary moderator in nuclear power plants. One of the fundamental aspects of this study was the need for very pure water in these circuits, to minimize corrosion of structural materials, and the incorporation of radionuclides into the water. This incorporation is responsible for increased radiation dose occupational workers. Water technology as an input of the nuclear industry, for skills, is required in the production and maintenance of water extremely clean. These capabilities are also used to provide solutions to the water supply to isolated rural communities, and small businesses to find alternatives to treat their effluents. Studies for this purpose have been channeled through a partnership with the National Universities of San Martín and Tucumán.